"LINGUISTIC-CULTURAL AND COMMUNICATIVE-PRAGMATIC CHARACTERISTICS OF PRAGMATONYMS" (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In recent years, the study of onomastic units, including pragmatonyms, in relation to individual characteristics of the human factor that created it, sociolinguistic environment, and extralinguistic factors such as folk culture and mentality, has become one of the most important issues in world linguistics. The anthropocentric paradigm that arose on the basis of these views fundamentally changed some of the conclusions formed within the framework of the immanent approach, and according to it, the person who owns the language (speech) was put in the main place. From this point of view, explanatory and etymological dictionaries of pragmatonyms created within the anthropocentric paradigm in world linguistics are of great practical importance for the development of the field.